Advancing the Science of Self‐Management in Adults With Long‐Term Left Ventricular Assist Devices. Issue 11 (25th March 2018) - Casida, Jesus; Aikens, James; Pagani, Francis; Ewald, Gregory; Craddock, Heidi; Pavol, Marykay; Schroeder, Sarah; Yang, James
Abstract: This study tested the applicability of the individual and family self‐management theory (IFSMT) to self‐management (SM) in patients with left ventricular assist devices (LVADs). From an existing data set, we extracted the following variables that correspond to IFSMT's conceptual dimensions: anxiety, depression, and cognition (context dimension); self‐efficacy (SM process dimension); adherence and quality of life (QOL; outcome dimensions). Descriptive statistics and partial least squares path modeling procedures were used for data analyses. A total of 100 patients (mean age 52 ± 13.4 years) with continuous flow LVAD designs comprised the present study. Most patients were White (78%), married (69%), college‐educated (72%), and on disability (53%). Their mean anxiety and depression scores were slightly above normal, while their cognitive function scores were slightly lower than normal. LVAD care self‐efficacy, adherence, and QOL were within normal ranges. Factor loadings ranged from 0.50 to 1.0, and there were significant forward path relationships among the context, process, and outcome dimensions (β ranges from 0.02 to 0.60, all P values < 0.05). In conclusion, the IFSMT provides a good fit for SM in LVAD. Further research is needed to clarify how best to improve LVAD SM practice and treatment outcomes.